2022
DOI: 10.3390/su14063548
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Criteria Assessment of the Economic and Environmental Sustainability Characteristics of Intermediate Wheatgrass Grown as a Dual-Purpose Grain and Forage Crop

Abstract: Kernza® intermediate wheatgrass [IWG; Thinopyrum intermedium (Host) Barkworth & Dewey] is a novel perennial cool-season grass that is being bred for use as a dual-purpose grain and forage crop. The environmental benefits of perennial agriculture have motivated the development of IWG cropping systems and markets for perennial grain food products made with Kernza, but the economic viability and environmental impact of IWG remain uncertain. In this study, we compared three-year cycles of five organic grain pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 63 publications
1
15
2
1
Order By: Relevance
“…The benefits of intercropping IWG with legumes were more related to an improvement on nutritive value than on the amount of total forage harvested. Although previous studies had shown increases in the total forage harvested in IWG intercropped with red clover (Favre et al, 2019;Law et al, 2022); in our experiment red clover biomass production did not compensate for the decrease in IWG biomass, resulting in similar total forage yields. The most promising legume to increase the total forage was Kura clover when it was planted with IWG together in the spring even though the greatest differences were seen after the first grain harvest (i.e., fall of the first grain production year and summer of the second grain production year).…”
Section: Croppingcontrasting
confidence: 91%
See 1 more Smart Citation
“…The benefits of intercropping IWG with legumes were more related to an improvement on nutritive value than on the amount of total forage harvested. Although previous studies had shown increases in the total forage harvested in IWG intercropped with red clover (Favre et al, 2019;Law et al, 2022); in our experiment red clover biomass production did not compensate for the decrease in IWG biomass, resulting in similar total forage yields. The most promising legume to increase the total forage was Kura clover when it was planted with IWG together in the spring even though the greatest differences were seen after the first grain harvest (i.e., fall of the first grain production year and summer of the second grain production year).…”
Section: Croppingcontrasting
confidence: 91%
“…Intercropping IWG with red clover has consistently increased the nutritive value of the summer and fall forage and tripled the amount of available forage in the fall (Favre et al, 2019), positively affecting the revenue perceived by the farmers. In fact, it has been seen that higher forage yields achieved by IWG-legume intercropping systems reduce the Kernza grain price required to be profitable (Law et al, 2022). Although Kernza R grain markets are in a price discovery phase, estimating potential net returns could be useful to compare different cropping systems.…”
Section: Introductionmentioning
confidence: 99%
“…Dewey] is a perennial cool-season grass being domesticated to produce a grain marketed as Kernza R (DeHaan et al, 2018) with the first commercial variety, "MN-Clearwater, " released in 2020 (Bajgain et al, 2020). The crop has potential to provide economic return for producers (Hunter et al, 2020a,b;Law et al, 2022) while reducing NO − 3 leaching compared to corn (Jungers et al, 2019). Intermediate wheatgrass initiates growth earlier in the season than warm-season forage and bioenergy grasses and is thus better able to reduce NO − 3 -N losses early in the season (Jungers et al, 2019) when losses are typically the highest in the Upper Midwest (Randall and Mulla, 2001;Crews and Peoples, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These "yield-gap" scenarios may be associated with soil degradation, strong disease pressure, or low commodity prices, combined with high input costs making production uneconomic, and could complement existing agricultural practice. Therefore, the reduction in input costs, the long-term environmental benefits, and potential dual-use options associated with perennial grain crops, including intermediate wheatgrass, could offset their lower productivity, for which economic analysis has begun (Law et al, 2022).…”
Section: Promoting and Identifying Opportunities For Perennial Grains...mentioning
confidence: 99%
“…When questioned about their motivations to trial intermediate wheatgrass, growers indicated that their primary areas of interest were improved soil health and microbial communities, reduced tillage requirement, the value of the crop in intercropping and weed suppression, and general interest in the value of perennials on-farm (Lanker et al, 2019;Meijer, 2020). Additionally, following grain harvest regrowth of leaves and stems may be used for grazing livestock, forage, hay, or bedding, or as biomass for biofuel production, potentially increasing the economic return, while the crop's extensive root system would improve soil structure (Ryan et al, 2018;Law et al, 2022).…”
Section: Promoting and Identifying Opportunities For Perennial Grains...mentioning
confidence: 99%